2002
DOI: 10.1210/en.2002-220363
|View full text |Cite
|
Sign up to set email alerts
|

[1-Deamino-4-Cyclohexylalanine] Arginine Vasopressin: A Potent and Specific Agonist for Vasopressin V1b Receptors

Abstract: To date, there are no vasopressin (VP) agonists that exhibit a high affinity and selectivity for the VP V1b receptor with respect to the V1a, V2, and oxytocin receptors. In this study, we describe the synthesis and pharmacological properties of [1-deamino-4-cyclohexylalanine] arginine vasopressin (d[Cha4]AVP). Binding experiments performed on various membrane preparations revealed that d[Cha(4)]AVP exhibits a nanomolar affinity for V1b receptors from various mammalian species (rat, bovine, human). It exhibits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
94
1

Year Published

2006
2006
2010
2010

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(101 citation statements)
references
References 39 publications
6
94
1
Order By: Relevance
“…(Lowbridge et al, 1977;Grzonka et al, 1983), and [deamino-Cys 1 ,Val 4 ,D-Arg 8 ]-vasopressin (dVDAVP), a selective V2 receptor agonist (Sawyer et al, 1981), were purchased from Bachem (Bubendorf, Switzerland). [1-Deamino-4-cyclohexylalanine] arginine vasopressin (d [Cha 4 ]AVP) (Derick et al, 2002) is a recently synthesized selective V1b receptor agonist and HOPhaa-D-Tyr(Me)-Phe-Gln-Asn-Arg-Pro-Arg-NH 2 (VPA) is a selective V1a receptor antagonist (Manning et al, 1992). Both were kindly donated by Dr. M. Manning (Department of Biochemistry and Molecular Biology, Medical College of Ohio, Toledo, OH).…”
Section: Methodsmentioning
confidence: 99%
“…(Lowbridge et al, 1977;Grzonka et al, 1983), and [deamino-Cys 1 ,Val 4 ,D-Arg 8 ]-vasopressin (dVDAVP), a selective V2 receptor agonist (Sawyer et al, 1981), were purchased from Bachem (Bubendorf, Switzerland). [1-Deamino-4-cyclohexylalanine] arginine vasopressin (d [Cha 4 ]AVP) (Derick et al, 2002) is a recently synthesized selective V1b receptor agonist and HOPhaa-D-Tyr(Me)-Phe-Gln-Asn-Arg-Pro-Arg-NH 2 (VPA) is a selective V1a receptor antagonist (Manning et al, 1992). Both were kindly donated by Dr. M. Manning (Department of Biochemistry and Molecular Biology, Medical College of Ohio, Toledo, OH).…”
Section: Methodsmentioning
confidence: 99%
“…This difference suggested that a Leu or a Pro at position 7 significantly modified the physical properties of the peptides. Oxidized synthetic and native Con-T were indistinguishable when co-injected in a C 18 Phenomenex analytical RP-HPLC column (Fig. 1D).…”
Section: Isolation and Sequencing Of Conopressin-t-amentioning
confidence: 99%
“…Conopressin-T was purified from fraction 30 using a 1% linear gradient of 0 -60% solvent B in A over 60 min (A ϭ 0.05% trifluoroacetic acid (aqueous); B ϭ 0.045% trifluoroacetic acid, 90% acetonitrile) on an analytical C 18 Phenomenex column. The flow rate was 1 ml/min, and the absorbance was monitored at 214 nm.…”
Section: Materials-t-butoxycarbonylmentioning
confidence: 99%
See 1 more Smart Citation
“…YM087 display high affinity for both human V1a and V2 receptors (Tahara et al, 1998). d [Cha 4 ]AVP is selective only for the human and bovine V1b receptors (Derick et al, 2002), while d[Leu 4 ,Lys 8 ]VP has high affinity for the rat V1b receptor (Pena et al, 2007). (2-methyl-1,4,5,6-tetrahydroimidazo[4,5- Harmar et al, 1998) are activated by the endogenous peptides VIP, PACAP-38, PACAP-27, peptide histidine isoleucineamide (PHI), peptide histidine methionineamide (PHM) and peptide histidine valine (PHV).…”
Section: Ensembl Id Ensg00000181408mentioning
confidence: 99%